Characterization of inhalable endotoxin, glucan, and dust exposures in Iowa farmers. - Sauvé, Jean-François (Int J Hyg Environ Health, 2020)
BACKGROUND: The observed deficit of lung cancer in farmers has been partly attributed to exposure to organic dusts and endotoxins based largely on surrogate metrics. To move beyond these surrogates for etiologic studies, we characterized task-based and time-weighted average (TWA) exposure to inhalable endotoxin, (1→3)-β-D-glucan, and dust in Iowa farmers. METHODS: We collected 320 personal inhalable dust samples from 32 farmers during 69 sample days in 2015 and 2016. Samples were collected using Button aerosol samplers and analyzed for endotoxin using a kinetic chromogenic amebocyte lysate assay, and for (1→3)-β-D-glucan using a Limulus endpoint assay. We assessed relationships between bioaerosol concentrations and selected tasks and farm characteristics using linear mixed-effects models. RESULTS: Bedding work, hog handling, and working in barn/confinement buildings, grain bins, and grain elevators were associated with higher endotoxin exposure. We found a monotonic trend between higher endotoxin concentrations and increasing number of animals. Bedding work, cleaning, and feed/grain storage work were associated with higher (1→3)-β-D-glucan concentrations. The median concentrations by task spanned a 400-fold range for endotoxin, a 600-fold range for (1→3)-β-D-glucan, and an 8-fold range for inhalable dust. Pearson correlations between endotoxin and glucan concentrations were 0.22 for TWA exposure and 0.56 for task samples. CONCLUSIONS: This characterization of exposure factors that influence bioaerosol concentrations can support the development of refined bioaerosol exposure metrics for future etiologic analyses of cancer and other health outcomes in farmers.